2017
DOI: 10.1007/s11892-017-0948-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Technology-Assisted Interventions for Diabetes Prevention

Abstract: This review focuses on studies that have examined the use of mobile phone text messaging, smartphone/web-based apps, and telehealth programs to help prevent or delay the onset of incident type 2 diabetes. While there is variability in the results of studies focused on technology-assisted DPP and weight loss interventions, there is evidence to suggest that these programs have been associated with clinically meaningful weight loss and can be cost-effective. Patients who are at risk for diabetes can be offered te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 51 publications
4
66
0
2
Order By: Relevance
“…Although mobile technology is being widely applied in clinical management of a variety of long-term chronic disorders [6,7,10,11,24,25] and also in modifying behaviour patterns such as smoking [26], the number of randomised intermediate and long-term studies in prevention of diabetes is limited. In this 2 year RCT involving 2062 participants with prediabetes recruited in two countries, India and the UK, with different ethnic and socio-cultural backgrounds, we have shown that delivery of a behavioural intervention by mobile technology is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Although mobile technology is being widely applied in clinical management of a variety of long-term chronic disorders [6,7,10,11,24,25] and also in modifying behaviour patterns such as smoking [26], the number of randomised intermediate and long-term studies in prevention of diabetes is limited. In this 2 year RCT involving 2062 participants with prediabetes recruited in two countries, India and the UK, with different ethnic and socio-cultural backgrounds, we have shown that delivery of a behavioural intervention by mobile technology is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to a growing body of evidence supporting the use of mHealth technology for improving physical activity levels, weight loss, and diabetes prevention [12]. A smartphone/web-based DPP (Alive-PD) that included tailored goal setting, weekly tracking, human-based phone coaching, and twice-weekly DPP curriculum achieved A1C reductions of 0.26% and 3.3 kg weight loss at 6 months [14].…”
Section: Discussionmentioning
confidence: 90%
“…Various digitally-supported interventions have been used for diabetes prevention and weight loss, including email, voice calls, text messaging, web-based applications, mobile apps, activity monitors, and telemedicine [12]. In fact, the Centers for Disease Control and Prevention (CDC) has recently started to recognize virtual programs as valid DPPs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, attendance continues to be a challenge for these types of programs and future studies should continue to explore strategies to improve overall attendance rates. In particular, the use of automated tracking tools (i.e., Fitbit, pedometers) have shown some early promise (36). Translating research into policy and practice is both a need and a challenge.…”
Section: Discussionmentioning
confidence: 99%